Determinats factors self-management barriers: characteristics, spiritual well-being, and religiosity in type 2 diabetes patients - Syabariyah, Sitti; Dewi, Inggriane Puspita; Lestari, Ida Sri; Sajodin, Sajodin; Suwandi, Nur Rohmah (Intelektual Pustaka Media Utama, 2024)
Holistic nursing needs to evaluate barriers to self-management, insight from characteristics, religiosity, and spiritual well-being to understand and address the multifaceted needs of individuals with chronic conditions, such as diabetes mellitus type 2. This study aimed to identify the determining factors that affect the barriers to self-management and the variables affecting them among Indonesian patients with T2DM. A cross-sectional survey was conducted among 101 patients recruited via purposive sampling from March to May 2023. The research instruments used were the Spiritual Well-Being Scale, Islamic Religiosity Scale, and Summary of Diabetes Self-Care Activities. The potential multicollinearity effects among the predictors of the barriers to self-management were also evaluated using multiple linear stepwise regression and collinearity analysis of variable inflation factors (VIFs). Most of the respondents had moderate spiritual well-being (52.2%) and high Islamic religiosity (60.4%) but also had barriers to self-management (55%). The F value of 5.888 with a probability of 0.004 (<0.05) showed that based on their regression coefficients, spiritual well-being, and Islamic religiosity simultaneously affected the barriers to self-management by 10.7%. The determinants that were found to affect the barriers to self-management were spiritual well-being and religiosity. These results suggest that it is necessary to develop an intervention model to improve the self-management of T2DM with a holistic approach.